Dykha O.V. Boudary lubrication in the sliding tribo systems of the car engines. - Диха, О.В. (Problems of Tribology, 2017)
The analysis of friction units of engines is carried out. It has been established that virtually all frictional frictions of engines during start-up and stop are in the state of boudary lubrication with the predominant influence of engine start-ups on the demolition of cylinders and bearings of the crankshaft. In the analysis of boudary lubrication from the point of view of chemistry, it has been established that the lubricating film consists of one or more layers of polar molecules located on the perpendicular solid surface. It is noted that the generalized dependences of the friction coefficient on temperature are more indicative for understanding the processes under way than for practical use.Key words: boudary lubrication, slip friction knots, engine, wear, transition temperatures.